Mahadji Sindhia and North Indian affairs (1785-1794) Vol.1 - Sarkar,Jadunath (ed.) (New Delhi Nation press, 2024)
Mahadji Sindhia and North Indian Affairs : 1785-1794 (Volume-1)
Keywords: Maratha history